Marketing Strategies and Students' Enrollment in Private Schools - Thapa, Hem Bahadur; Chhetri, Tikaram (SNPRC Journal, 2025)
This paper explores the impact of marketing strategies on students’ enrollment in the private school of Sainamaina Municipality. It employed a quantitative approach and a descriptive research design. The dependent variable is student enrollment, whereas the independent factors were media advertisements, pricing, in-person interactions, infrastructure development, and highquality programs. Among other things, the study examined research gaps, conceptual and theoretical reviews, and reviews of relevant studies in order to investigate student enrollment. Multiple regression analysis used to explore the causal relation between Sainamaina Municipality's private school enrollment rates and marketing tactics. The study examined a significance effect and relationship between marketing strategies with quality of the programs, use of social media and development of infrastructures, counseling, media advertisement and fee on enrollment of students. The study suggested that the marketing activities should be implemented according to the budget within plan that helps to increase the students’ enrollment.